Politik Identitas Islam Indonesia Kontemporer: Radikalisme Islam Versus Moderatisme Islam dalam Politik Elektoral Pilpres 2019 (Contemporary Indonesian Islamic Identity Politics: Islamic Radicalism Versus Islamic Moderatism in the 2019 Presidential Election Electoral Politics) - Rubaidi Rubaidi; Dwi Setianingsih (Potret Pemikiran, 2021)
ABSTRACTThis article examines an important aspect that has not been widely studied in previous writings, namely the dimensions of the contestation of radical Islamic groups and moderate Islamic groups in the 2019 electoral political stage. The representation of radical Islam is represented by the GNPF-MUI which includes Islamic organizations such as FPI, FUI, Larkar Jihad and others. Meanwhile, moderate Islam is represented by Nahdlatul Ulama (NU), some Muhammadiyah and other moderate mass organizations. Behind the frenzy of "Action for Defending Islam" 411, 212, reunion 212, as well as other issues during the 2019 presidential election electoral campaign, there is actually an aspect of the contestation of the two camps in the struggle for Islam in the public sphere and in power politics. Radical Islamic groups carrying the spirit of nativism 'Islamic populism' voiced the agenda of 'political Islam' into the realm of state power through the Prabowo-Sandi camp. Meanwhile, identity political groups are still promoting 'Islam wasyatiyah' with the symbol of the Republic of Indonesia at a fixed price through the Jokowi-Amin camp. This article is based on a qualitative method with a literature study approach from various sources. From the contestation of the two groups, in the end, moderate Islam won, represented by the election of the Jokowi-Makruf Amin pair. Amin, no doubt, does represent the moderate current of Islam where he previously served as Rais Aam of the Nahdlatul Ulama (PBNU) Executive Board. In addition, the pair's victory shows that the dynamics of moderate Islam in Indonesia are still embraced by the majority of Muslims in Indonesia.Keywords: Identity politics; Radical Islam; moderate Islam; 2019 presidential election. ABSTRAK Artikel ini menelaah tentang aspek penting yang belum banyak dikaji tulisan-tulisan sebelumnya, yakni dimensi kontestasi kelompok radikal Islam dan kelompok Islam moderat dalam panggung politik elektoral 2019. Representasi dari Islam radikal diwakili GNPF-MUI yang di dalam terdapat ormas Islam seperti FPI, FUI, Larkar Jihad dan sebagainya. Sedangkan, Islam moderat direpresentasi oleh ormas Nahdlatul Ulama (NU), sebagian Muhammadiyah dan ormas moderat lainnya. Di balik hingar-bingar “Aksi Bela Islam” 411, 212, reuni 212, maupun isu lain selama kampanye politik elektoral Pilpres 2019, sesungguhnya terdapat aspek kontestasi dua kubu tersebut dalam perebutan Islam dalam ruang publik maupun politik kekuasaan. Kelompok Islam radikal mengusung semangat nativisme ‘populisme Islam’ menyuarakan agenda ‘Islam politik’ ke dalam ranah kekuasaan negara melalui kubu Prabowo-Sandi. Sedangkan, kelompok politik identitas tengah tetap menggelorakan ‘Islam wasyatiyah’ dengan simbol NKRI harga mati melalui kubu Jokowi-Amin. Artikel ini berbasis metode kualitatif dengan pendekatan studi literatur dari berbagai sumber. Dari kontestasi kedua kelompok tersebut, pada akhirnya dimenangkan oleh Islam moderat yang direpresentasi melalui terpilihnya pasangan Jokowi-Makruf Amin. Amin, tidak diragukan, memang mewakili arus Islam moderat di mana ia sebelumnya menjabat sebagai Rais Aam Pengurus Besar Nahdlatul Ulama (PBNU). Selain itu, kemenangan pasangan ini menunjukkan dinamika Islam moderat di Indonnesia masih dianut mayoritas muslim di Indonesia.Kata kunci: Politik identitas; Islam radikal; Islam moderat; pilpres 2019.